Effect of difference in shot angle on set shot behavior in Basketball - Nagata, N.; Inomata, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Movement patterns in a motor task become more consistent with the skill development. However, it is assumed that the difference of task condition affect the variable of movement patterns while skill is same. Especially, motor programming may not consistent in the conditions for the relatively less experiences; therefore the variable of the movement patterns could be increased. The main purpose of this study was to examine the effect of difference in shot angle on set shot behavior in the basketball at semi-expert level. Method: Participants of this study were two male Japanese college basketball players (Participant A: 170cm, 22 years age, 12 years experiment of basketball, Left hand shooter, Guard position. Participant B: 172cm, 20 years age, 10 years experiment of basketball, Right hand shooter, Guard position). In this study, Shot made percentage was measured and shot hand movement was recorded by 2 digital cameras. Shot movement was analyzed by three dimensions motion analysis system. Participants were took 10 shots from two locations, which were arranged at Free throw distances (4m from the free throw line to basketball ring) at two angles (Front, Side). Between each trial, we set 1 minute as the rest interval. Results: In the front angle, Shot made percentage was Participant A = 60% and Participant B = 70%. In the side angle, Shot made percentage was Participant A = 60% and Participant B = 60%. In addition, the standard deviation of shot movement on the side angle was increased rather than the front angle. Discussion: These results suggested that the whole movement pattern has been adjusted while variability of each joint increased, therefore participants was able to shoot successfully.